The Implementation Model of a Consensual Refnancing Rate for the BRICS Countries - Zharikov, М. V. (Finansy: teoriâ i praktika (Online), 2019)
The relevance of the research subject is due to the fact that countries look for adaptive approaches to the turbulence of the international monetary system (IMS). The approaches of the BRICS countries to the IMS transformation have been fully studied in the economic literature. However, there are no researches on foundation of an advanced central bank as an alternative supranational monetary institution in the new international fnancial architecture. The article objective is to develop a mechanism for setting up the refnancing rate for the BRICS countries in case of the integration hypothesis the currency union, and the lender of last resort and the general unit of accounts. A liberal pricing method has been used to create the model. There is a hypothesis that the refnancing rate should be set at a higher level than that of the People’s Bank of China’s and lower than that of Brazil, Russia, India and South Africa’s, since it has comparative advantages in crediting. The mechanism of the consensual rate of the BRICS countries is based on the assumption that the amount of money in circulation may vary by an amount that does not cause negative consequences for national economies. The fundamental difference between the results of this study is in optimization of the credit resources ﬂow, which implies their distribution within certain limits and in several stages. The main provisions indicate that the optimal rate may provide a background for the coordination of monetary policies in the BRICS countries within the Central bank. The practical relevance of the model is that it can be used to establish the refnancing rate in the BRICS countries. The model suggests that the optimal crediting value in the BRICS countries should ft the GDP growth limits. To conclude, the optimal refnancing rate is a key issue in forming a monetary union and a common currency in the BRICS countries.